Climate-driven challenges in weed management for ornamental crop production in the United States: a review - Mou, Supti Saha; Haus, Miranda J.; Hayden, Zachary D.; Patterson, Eric L.; Saha, Debalina (Frontiers in Agronomy, 2025)
Climate change, driven by rising atmospheric carbon dioxide (CO2), increasing temperatures, and shifting precipitation patterns, is profoundly impacting agricultural systems worldwide. These environmental changes significantly affect weed growth, distribution, and management, posing challenges across agronomic, horticultural, and ornamental crops. This review explores the impacts of climate change on weeds, focusing on the differential responses of C3 and C4 weed species to elevated CO2, higher temperatures, and drought stress. It also examines how these climatic factors influence weed management practices, particularly herbicide efficacy. While much research has focused on agronomic crops, ornamental crop productions remain underexplored, despite their unique challenges. Ornamental production systems often involve diverse plant species grown in confined spaces, making weed management more complex and sensitive to herbicide residues. These challenges are compounded by the adaptability and invasiveness of weeds under changing climatic conditions. The review highlights critical knowledge gaps, particularly the limited understanding of how climatic factors impact weed physiology and herbicide performance in ornamental settings. Addressing these gaps is essential to develop climate-resilient strategies for sustainable weed management across diverse agricultural systems.